Family Involvement in School Transition: Chinese Migrant Families’ Experiences of Children Transitioning from Early Childhood Education to Primary School in New Zealand - Zhong, Guangming (Auckland University of Technology, 2023)
Children’s transition from early childhood education (ECE) to primary school is a complex phenomenon. School transition not only influences children in the first months of primary schooling it also has long-lasting impacts. The extent to which children feel successful in the transition process may influence how children approach their future educational transitions. School transition has been widely researched in New Zealand and internationally. However, no New Zealand research has investigated the school transition experiences of Chinese migrant families. This doctoral study fills an important research gap and provides empirical evidence regarding Chinese migrant families’ school transition in New Zealand. A qualitative interpretive research methodology was employed to unpack the complexity of the transition experiences of Chinese migrant families in New Zealand through interviews with ten Chinese migrant parents. Thematic analysis was utilised to identity key themes that emerged from the research data. Bronfenbrenner’s ecological systems theory, and the four principles of Te Whāriki, the New Zealand national early childhood curriculum, were employed as the theoretical framework to underpin data analysis. Scrutinising participant narratives of their perspectives and experiences of school transition in New Zealand, this study found participants’ perspectives on school transition were dynamic in nature. Chinese parents in this study typically valued the process of children’s school transition but had unique concerns and expectations towards transition. School transition was experienced differently by the Chinese parents in this study, in terms of the parenting practices that they engaged in to support school transition, the transition practices delivered by ECE centre and schools, and the challenges they encountered. Participants’ perspectives and experiences regarding school transition were influenced by multiple contextual elements, including perceived personalities and characteristics of children, parental educational beliefs, parents’ past experiences, parent-teacher communication, connection between ECE and school, family environments, financial status, parents’ social networks, and the broader educational, social, cultural, and political contexts of both China and New Zealand. This research highlights the need for individualised approaches that take account of families’ perspectives, concerns, and expectations, to support Chinese migrant families’ school transition in New Zealand.